2017
DOI: 10.1175/mwr-d-16-0092.1
|View full text |Cite
|
Sign up to set email alerts
|

The Development of a Terrain-Resolving Scheme for the Forward Model and Its Adjoint in the Four-Dimensional Variational Doppler Radar Analysis System (VDRAS)

Abstract: The four-dimensional Variational Doppler Radar Analysis System (VDRAS) developed at the National Center for Atmospheric Research (NCAR) is significantly improved by implementing a terrain-resolving scheme to its forward model and adjoint based on the ghost cell immersed boundary method (GCIBM), which allows the topographic effects to be considered without the necessity to rebuild the model on a terrain-following coordinate system. The new system, called IBM_VDRAS, is able to perform forward forecast and backwa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 37 publications
0
15
0
Order By: Relevance
“…The microphysics scheme in VDRAS combines a Kessler warm rain scheme and a simple ice scheme (Chang et al, ). In addition to its use as a research tool for convective‐scale analyses (Friedrich et al, ; Gochis et al, ; Sun, ; Sun & Zhang, ; Tai et al, ), VDRAS has been used for operational nowcasting in several forecasting offices since 2001 (Crook & Sun, ; Mueller et al, ; Sun et al, ; Sun & Crook, ). The observations assimilated in VDRAS are radial velocity and reflectivity from the six Doppler radars and the AWS network shown in Figure , whereas mesoscale forecast data from the National Center for Atmospheric Research's Weather Research and Forecast (WRF) model are used for first guesses and boundary conditions.…”
Section: Observational Data Vdras and Its Reanalysismentioning
confidence: 99%
“…The microphysics scheme in VDRAS combines a Kessler warm rain scheme and a simple ice scheme (Chang et al, ). In addition to its use as a research tool for convective‐scale analyses (Friedrich et al, ; Gochis et al, ; Sun, ; Sun & Zhang, ; Tai et al, ), VDRAS has been used for operational nowcasting in several forecasting offices since 2001 (Crook & Sun, ; Mueller et al, ; Sun et al, ; Sun & Crook, ). The observations assimilated in VDRAS are radial velocity and reflectivity from the six Doppler radars and the AWS network shown in Figure , whereas mesoscale forecast data from the National Center for Atmospheric Research's Weather Research and Forecast (WRF) model are used for first guesses and boundary conditions.…”
Section: Observational Data Vdras and Its Reanalysismentioning
confidence: 99%
“…VDRAS can retrieve mesoscale dynamical and thermodynamic fields with frequent updating of less than 20 min by assimilating radial velocity and reflectivity data from radar networks and surface observations from dense mesonets. It has been used for convective‐scale data assimilation research (Chang et al., 2016; Sun & Crook, 1994; Tai et al., 2017) and for severe convective events studies (Chang et al., 2014; Friedrich et al., 2016; Gochis et al., 2014; Sun & Zhang, 2008). The 3‐dimensional gridded high‐resolution and frequency updated analyses of meteorological fields created by VDRAS can provide valuable information for this study in which meso and convective‐scale dynamical processes play crucial roles.…”
Section: Introductionmentioning
confidence: 99%
“…The three-dimensional spatial correlation coefficient between the vertical velocity and vertical vorticity (calculated using Eq. (22) of Tai et al, 2017) within the VHTs inside four squares in Figure 9 is shown in Figure 10. The good spatial correlation between updrafts and cyclonic vorticities, as indicated by the fact that the spatial correlation coefficients between two variables are near 0.5 or above during 0900-1100 UTC, supports the existence of VHTs within the rainband of TC Fanapi.…”
Section: 1029/2018jd028281mentioning
confidence: 99%